2008
DOI: 10.1007/s11064-008-9762-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Thiopental and Pentobarbital on Spinal GABAA Receptors

Abstract: General anesthetics thiopental and pentobarbital possess very similar chemical structures whereas their clinical potency is quite different. The underlying molecular mechanism is not fully understood. This study was designed to assess the differential effects of thiopental and pentobarbital on GABA(A) receptors of mechanically dissociated rat spinal dorsal horn neurons by using whole-cell patch-clamp technique. Pentobarbital, at a concentration of 30 microM, which markedly enhanced sub-saturated GABA-induced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…In the presence of PHB (300 µM), neither FLM nor chlorotoxin could overcome the PHB-mediated inhibition of I K(erg) activated by long-lasting membrane hyperpolarization ( Figure 3 D). The results suggested that PHB-induced inhibition of I K(erg) in these cells is unlinked to its propensity to interact with GABA A receptors, as reported previously in other cell types [ 7 , 9 , 33 , 47 , 48 , 49 , 50 ].…”
Section: Resultssupporting
confidence: 76%
“…In the presence of PHB (300 µM), neither FLM nor chlorotoxin could overcome the PHB-mediated inhibition of I K(erg) activated by long-lasting membrane hyperpolarization ( Figure 3 D). The results suggested that PHB-induced inhibition of I K(erg) in these cells is unlinked to its propensity to interact with GABA A receptors, as reported previously in other cell types [ 7 , 9 , 33 , 47 , 48 , 49 , 50 ].…”
Section: Resultssupporting
confidence: 76%